The Skin Reservoir Model: A Tool for Evaluating Microdialysis Sampling of Large Biomarkers from Human Skin - Katrine Baumann; Sidsel Falkencrone; Niels Peter Knudsen; Anders Woetmann; Sally Dabelsteen; Per Stahl Skov (Medical Journals Sweden, 2020)
Microdialysis is a well-established technique for sampling of small molecules from the human skin, but larger molecules are more difficult to recover. Consequently, sampling feasibility must be evaluated before microdialysis is used in vivo. This report presents a tool for estimating the recovery of large biomarkers from human skin by microdialysis, using previously frozen human skin specimens as reservoirs for biomarker reference solutions. Recovery of the following 17 biomarkers was assessed: CCL27/CTACK, CXCL1/GROα, CXCL7/NAP-2, CXCL10/IP-10, EGF, GM-CSF, IFN-γ, IL-1α, IL-6, IL-8, IL-17, IL-22, IL-23, MIF, TNF-α, TSLP and VEGF. The relative skin recoveries of 13/17 biomarkers were successfully determined in the range 4.0-18.4%. Sampling in the skin reservoir model was not associated with probe leakage, as fluid recovery was stable, at between 80% and 110%. Furthermore, the skin reservoir model enabled studies and optimization of different parameters known to affect biomarker recovery, including flow rate and perfusate composition.